Bidirectional superior cavopulmonary anastomosis with or without cardiopulmonary bypass: A randomized study. Issue 6 (21st May 2017) - Talwar, Sachin; Gupta, Anish; Nehra, Ashima; Makhija, Neeti; Kapoor, Poonam Malhotra; Sreenivas, Vishnubhatla; Choudhary, Shiv Kumar; Airan, Balram
Abstract: Objectives: This study aims to compare the bidirectional superior cavopulmonary anastomosis (BDG) with or without cardiopulmonary bypass (CPB). Methods: 100 patients undergoing BDG were randomized into two groups: Off‐CPB or on‐CPB groups. All patients underwent near‐infrared spectrophotometry (NIRS) and bispectral index (BIS) monitoring and pre‐ and postoperative serum 100 beta protein measurements (Sβ100) and neuro‐cognitive evaluation. Postoperative intensive care unit (ICU) parameters were also studied. Results: The median age of patients in the on‐CPB and off‐CPB group were 42 and 48 months, respectively (p = 0.11). Median weights in the on‐CPB group and off‐CPB group were 13.5 (5‐50) kg and 15 (7‐36) kg, respectively (p = 0.927). There was a significant rise in superior vena cava (SVC) pressure on SVC clamping in the off‐CPB group (23.12 ± 6.84 vs 2.98 ± 2.22 mmHg) on‐CPB group (p < 0.001). There was a significant fall in NIRS and BIS values from baseline in the off‐CPB group during the anastomosis but there was no statistically significant change in serum Sβ100from pre‐clamp to post‐clamp in either group. Inotropic support, duration of ventilation, ICU stay, and hospital stay were significantly less in the off‐CPB group (p < 0.001). Assessment of Social Adaptive Functioning revealed no adverse sequelae. There were significant cost savings if surgery was performed off‐CPB (p < 0.001). Conclusion: Off CPB‐BDG is an economical and safe procedure. Duration of inotropic and mechanical ventilatory support, ICU, and hospital stay is significantly less. We did not observe any early adverse neurologic sequelae in patients undergoing off‐CPB BDG.